Efeito do aquecimento com corrida sobre a agilidade e a impulsão vertical em jogadores juvenis de futebol - Constantino Coledam, Diogo Henrique [UNESP]; Talamoni, Guilherme Augusto [UNESP]; Cozin, Mauricio; dos-Santos, Julio Wilson [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
The aim of this study was to evaluate the effect of warm-up on agility (AG) and on vertical jump (VJ) tests in youth soccer players. Sixteen players performed the AG and VJ tests without warm-up (NW) and with warm-up (WW) randomly, within two weeks, at least 48 h interval, during season. The warm-up was performed only a light running during 10 min. The paired t-test identified significant difference (p <0,05) between the NW and WW conditions in the tests of SR and CJ (9,14 +/- 0,28 vs 8,94 +/- 0,30 s e 51,4 +/- 4,2 vs 54,5 +/- 6,4 cm, respectively). The warm-up performed on light intensity running was effective to improve the AG and VJ tests performance in youth soccer players.

O objetivo deste estudo foi verificar o efeito do aquecimento sobre os testes de agilidade (AG) e de impulsão vertical (IV) em jogadores de futebol juvenis. Dezesseis jogadores realizaram os testes de AG e de IV (n=16) sem aquecimento (SA) e com aquecimento (CA), de maneira randômica, em duas semanas, com pelo menos 48 h de intervalo, durante o período de competição. O aquecimento foi realizado apenas com uma corrida leve de 10 min. O test-t pareado identificou diferença significativa (p<0,05) entre as condições SA e CA nos testes de AG e IV (9,14±0,28 vs 8,94±0,30 s e 51,4±4,2 vs 54,5±6,4 cm, respectivamente). O aquecimento com corrida de intensidade leve melhorou o desempenho nos testes de AG e IV em atletas juvenis de futebol.
Effect of running warm-up on agility and vertical jump in young soccer players
Keywords: Agility; Warm-up; Running; Soccer; Vertical Jump